Dificultades teórico metodológicas de la propuesta intercultural de Raúl Fornet Betancourt (2015)
I can hardly do justice in these few lines to the already extensive work done in recent years by Raúl Fornet-Betancourt. It would be useless even trying to do it. Instead, I want to concentrate on some of his most significant contributions to highlight the most interesting things and express with rigorously and fraternally, perhaps some fruitful suggestions in view of future work. Everything as an enthusiast way to join the deserved tribute for his first sixty years of life was organized by other dear friends, including Sidekum Antonio, who has been kind for inviting me to participate. So I thought it is appropriate to break down the exhibition in three sections of unequal length: history, criticism and objections